Hubungan Pengetahuan Ibu dengan Kelengkapan Imunisasi Dasar pada Anak di Posyandu Raden Omas - Oktaviani Delvi; Fatya Nurul Hanifa; Selasih Putri Isnawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Immunization is one of the most effective and efficient public health efforts in preventing diseases and reducing mortality rates in children such as smallpox, polio, tuberculosis, hepatitis B, diphtheria, measles, rubella, congenital rubella syndrome (CRS), tetanus, pneumonia (lung inflammation) and meningitis (inflammation of the brain membrane) (Nandi & Shet, 2020). Data from the Indonesian Ministry of Health in 2020 showed that vaccination coverage in the 3rd and 4th months was months. However, efforts can be made to increase child vaccination coverage to 80% and that does not include DT, MR2, and HPV vaccinations. As, measles data is only 45%, diphtheria-tetanus (DT) is around 40% (Indonesian Ministry of Health, 2021). To determine the relationship between maternal knowledge and the completeness of basic immunization in children at the Raden Omas Posyandu. This study uses a quantitative research design with a cross-sectional method. The population in this study consisted of mothers who had children aged 12 to 18 months at Posyandu Raden Omas, totaling 36 mothers. The statistical results showed a relationship between maternal knowledge and the completeness of basic immunization in children p-value (0.048). Most respondents had good knowledge, as many as 13 respondents (36.1%). Sufficient knowledge, as many as 13 respondents (36.1%). Insufficient knowledge, as many as 10 respondents or 27.8%. Most respondents had incomplete immunization, namely 18 respondents (50%).